GE_GERICHTE C/8913/2011 vom 4. Oktober 2012 - GE Cour de justice (2012)
; DÉFAUT(CONTUMACE) ; REPRÉSENTATION ; DROIT À LA PREUVE ; DROIT D'ÊTRE ENTENDU ; PRINCIPE DE LA BONNE FOI | CPC.152.1 CPC.234.1 CPC.243.1